2023
DOI: 10.1002/epi4.12687
|View full text |Cite
|
Sign up to set email alerts
|

Sleep architecture in drug‐naïve adult patients with epilepsy: Comparison between focal and generalized epilepsy

Abstract: Objective: Sleep impairment is one of the most common comorbidities affecting people with epilepsy (PWE). The bidirectional relation between epilepsy and sleep has been widely established. Several studies investigated subjective sleep quality and daytime vigilance in PWE, highlighting frequent complaints of sleep fragmentation, difficulties in falling asleep, and daytime sleepiness. The present study aimed to evaluate sleep structure in drug-naive PWE, distributed on the basis of epilepsy type, and compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…11,16,107 Recent data also include the increased frequency of sleep stage shifts in PWE, coupled with more frequent wake bouts, producing sleep instability, lack of sleep continuity, and REM sleep impairment. 21 Sleep fragmentation has been previously associated with changes in orexin neurotransmission in animal models and human studies 40,[108][109][110][111] and, although in a purely hypothetical model, it is conceivable that sleep impairment in PWE may be associated with increased orexin expression and function and that this neurotransmission overactivity can, in turn, impair sleep and possibly trigger IEDs and seizures (Figure 3). Therefore, antagonisms to orexin receptors may represent a strategy for improving sleep and thus seizures in PWE.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…11,16,107 Recent data also include the increased frequency of sleep stage shifts in PWE, coupled with more frequent wake bouts, producing sleep instability, lack of sleep continuity, and REM sleep impairment. 21 Sleep fragmentation has been previously associated with changes in orexin neurotransmission in animal models and human studies 40,[108][109][110][111] and, although in a purely hypothetical model, it is conceivable that sleep impairment in PWE may be associated with increased orexin expression and function and that this neurotransmission overactivity can, in turn, impair sleep and possibly trigger IEDs and seizures (Figure 3). Therefore, antagonisms to orexin receptors may represent a strategy for improving sleep and thus seizures in PWE.…”
Section: Discussionmentioning
confidence: 98%
“…21 In this research, patients with focal epilepsy presented an increase in stage 2 of non-REM (NREM) sleep (N2) and wake after sleep onset and a decrease in REM, with consequent fragmentation of the sleep structure, compared to controls. 21 Previous studies showed that REM sleep presents an antiepileptic effect due to the reduction of ictal and interictal epileptic discharges (IEDs) in this sleep stage. It was consequently hypothesized that there is an important role of REM sleep in regulating the epileptic spiking threshold and hampering the risk of seizures.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations